Ape Maze “A Dice Adventure” Inovasi Pembelajaran Dalam Meningkatkan Keterampilan Berfikir Kritis Anak Usia Dini - Samsul Hakim; Hadlun; Mariana, Siti (STAI Al-Amin Gersik Kediri Lombok Barat NTB, 2025)
Critical thinking skills in early childhood are an important foundation for their cognitive and social development. However, based on observations at RA Usman Baharun Ba'alawi Bengkel, many children still face difficulties in identifying problems, analyzing information, and making conclusions. This situation indicates the need for innovation in learning methods that can facilitate the development of these skills. This study aims to describe and analyze the application and effectiveness of APE Maze “A Dice Adventure” in early childhood learning. The first objective is to provide a clear picture of how this APE is implemented in the classroom and how children respond to this learning method. The second objective was to measure the effectiveness of this APE in improving children's critical thinking skills, using observational data and qualitative measurements. This study uses a quantitative descriptive approach to get a clear picture of the effectiveness of using APE Maze “A Dice Adventure”. This method was chosen because it allows researchers to collect and analyze numerical data obtained from observations and measurements. quantitative approaches are very effective in measuring changes or the impact of an intervention. The results showed that the use of APE Maze “A Dice Adventure” had a positive impact on the learning process and the development of children's critical thinking skills. Based on the observation results, there is a significant increase in children's ability to identify problems, analyze information, and make conclusions.